2014
DOI: 10.1080/01634372.2013.860652
|View full text |Cite
|
Sign up to set email alerts
|

The Highs and Lows of Caregiving for Chronically Ill Lesbian, Gay, and Bisexual Elders

Abstract: This study examines informal caregivers’ and LGB care recipients’ “best” and “worst” experiences of care within their relationship. Communal relationship theory guides the research. The work uses qualitative interview data from a sample of 36 care pairs (n=72), divided between committed partners and friends, to understand the similarities and differences in the care norms employed in varied relationship contexts. Findings from the study show that relationship context influences the experiences that caregivers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 28 publications
0
31
0
Order By: Relevance
“…In contrast to the dominant literature, only 1 mentioned adult children. These findings also highlight the unique role friends—sometimes conceptualized as “chosen family”—can and do play in gay, bi, lesbian, and transgender (LGBT) social networks . Many men mentioned wanting a specific group for GBMPCa where they felt more shared experiences with the other members of the group.…”
Section: Discussionmentioning
confidence: 87%
“…In contrast to the dominant literature, only 1 mentioned adult children. These findings also highlight the unique role friends—sometimes conceptualized as “chosen family”—can and do play in gay, bi, lesbian, and transgender (LGBT) social networks . Many men mentioned wanting a specific group for GBMPCa where they felt more shared experiences with the other members of the group.…”
Section: Discussionmentioning
confidence: 87%
“…Among LGBTQ older adults, 20% indicated that they were currently providing informal care [80]; caregivers reported a strong sense of duty [38], but also love and commitment, particularly among caring spouses, partners, and close friends [48]. Relationship quality was protective against depression for both informal caregivers and those receiving care [62].…”
Section: Resultsmentioning
confidence: 99%
“…A 2015 report by the National Alliance for Caregiving and the American Association of Retired Persons (AARP) Public Policy Institute indicated that among approximately 1000 care receivers aged 50 years and older, about 63% suffer from long-term physical conditions and 34% have short-term physical conditions, as well as mental conditions necessitating care include memory problems (29%), emotional and mental health problems (19%), behavioral issues (5%), and developmental and intellectual disorders (3%). In addition, because friends also play significant roles in the informal caring system, they are frequently included in family caregiving studies (Fine, 2012;Himes & Reidy, 2000;Muraco & Fredriksen-Goldsen, 2014;Penning & Wu, 2015).…”
Section: Snapshot On Family Caregivingmentioning
confidence: 99%